Pengaruh Game-Based Learning Terhadap Motivasi dan Prestasi Belajar - Komang Redy Winatha; I Made Dedy Setiawan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
The curriculum requirement requires the lecturer to be creative in developing the learning style. However, in interpersonal skill subject, the lecturer only provides things that available on the textbook conventionally and focusing on the material accomplishment of the curriculum without considering the learning expected output. To resolve that problem, the lecturer needs to modify the learning style by providing a learning innovation. One of the alternatives is implementing game-based learning model by playing media card. Therefore, the research objective was to describe positive effect of game-based learning model towards collegian’s learning motivation and achievement in Interpersonal Skill subject in STMIK STIKOM Indonesia. The research method used was Quasi-Experiment with non-equivalent control group design. The research instrument used was a motivation questionnaire and learning achievement test. The research result showed that there was a positive effect of game-based learning model towards Collegian’s motivation and learning achievement in Interpersonal Skill subject.